Positive electrode material for lithium ion secondary battery, method for producing same, positive electrode for lithium ion secondary battery, and lithium ion secondary battery
By adding calcium phosphate and aluminum phosphate particles to the lithium iron phosphate positive electrode material of lithium ion secondary batteries, the problem of low discharge capacity ratio of lithium iron phosphate during high-risk discharge is solved, and the high input and output characteristics and charge and discharge characteristics are improved.
Patent Information
- Application Number
- CN202380066367.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-22
- Filing Date
- 2023-07-12
- Publication Date
- 2025-04-25
AI Technical Summary
Lithium iron phosphate discharge is not high during high-rate discharge, and coarse aggregated particles are easily formed during sintering and carbonaceous coating, affecting electrochemical reactivity and charge and discharge characteristics.
The calcium phosphate and aluminum phosphate particles are added to the cathode material of lithium iron phosphate, and the content and distribution of Ca and Al are controlled during the manufacturing process to inhibit the sintering of primary particles and the formation of aggregation particles with high surface area.
The input and output characteristics of lithium-ion secondary batteries are improved, the electrochemical reactivity and charge and discharge characteristics are enhanced, the formation of coarse particles is reduced, and the overall performance of the battery is improved.
Smart Images

Figure CN119895593A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a positive electrode material for a lithium ion secondary battery and a method for producing the same, a positive electrode for a lithium ion secondary battery, and a lithium ion secondary battery. Background Art
[0002] Compared with lead batteries and nickel-metal hydride batteries, lithium-ion secondary batteries have higher energy density and output density, and are used in a variety of applications, including home backup power supplies for small electronic devices such as smartphones, power tools, etc. In addition, large-capacity lithium-ion secondary batteries are being promoted for use in vehicles such as electric vehicles and for storage of renewable energy such as solar power generation and wind power generation.
[0003] Lithium-ion secondary batteries have at least a positive electrode, a negative electrode, and an electrolyte. As electrode materials constituting the positive electrode, lithium metal composite oxides having the property of being able to reversibly embed / extract lithium ions, such as lithium cobalt oxide (LiCoO2) or lithium manganese oxide (LiMn2O4) belonging to oxide-based positive electrode materials, and lithium iron phosphate (LiFePO4) belonging to olivine-based positive electrode materials, can be used. Improvements have been made from various viewpoints such as high capacity, long life, improved safety, and low cost of the battery.
[0004] The aforementioned lithium iron phosphate (LiFePO4) uses iron, which is abundant and cheap, and is therefore a material that is easy to achieve low cost. In addition, lithium iron phosphate has excellent properties that are lacking in oxide-based positive electrode materials represented by lithium cobalt oxide, such as the strong covalent bond between phosphorus and oxygen, and no oxygen is released at high temperatures, thus having excellent safety.
[0005] On the other hand, lithium iron phosphate has an olivine structure and thus has problems such as low Li ion diffusivity, low electron conductivity, and inferior input-output characteristics compared to oxide-based positive electrode materials.
[0006] In order to improve the input-output characteristics of lithium iron phosphate, it has been proposed to improve the diffusibility of Li ions and the electronic conductivity by making lithium iron phosphate particles fine and coating the surfaces of the individual particles with a conductive carbonaceous film.
[0007] For example, Patent Document 1 proposes a positive electrode active material for a non-aqueous electrolyte battery comprising primary particles having an Al compound present in at least a portion of the grain boundaries of polycrystalline particles having an olivine crystal structure and a chemical composition represented by the following general formula (1).
[0008] LiFePO4(1)
[0009] Prior art literature
[0010] Patent Literature
[0011] Patent Document 1: Japanese Patent Application Publication No. 2009-032678 Summary of the invention
[0012] Problem that the invention aims to solve
[0013] According to Patent Document 1, the ratio of the discharge capacity obtained during high-rate discharge to the discharge capacity obtained during low-rate discharge can be increased.
[0014] In the primary particles proposed in Patent Document 1, the Al compound is present in at least a portion of the grain boundaries of the polycrystalline particles. In the process of generating the primary particles, the crystal growth of the phase having the crystal structure is suppressed, thereby forming a state where a large number of crystal grains exist, and the surface area of the phase having the crystal structure is increased compared to the past. As a result, the electrochemical reactivity is increased, and the discharge capacity ratio is improved.
[0015] However, lithium iron phosphate has the following problems: even if the growth of primary particles is suppressed, the primary particles will sinter during the synthesis by firing and during the heat treatment when covered with the conductive carbonaceous film, and will easily form coarse aggregated particles. On the other hand, although there is also a method of mechanically crushing and refining the lithium iron phosphate covered with the conductive carbonaceous film, the following problems will arise: the crystallinity will be reduced due to the crushing, and the carbonaceous film will be peeled off from the surface of the primary particles, and sufficient charge and discharge characteristics cannot be achieved.
[0016] In view of the problems of the above-mentioned prior art, one aspect of the present invention is to provide a positive electrode material containing lithium iron phosphate having high input-output characteristics when used as a positive electrode of a lithium ion secondary battery, a method for manufacturing the same, a positive electrode for a lithium ion secondary battery, and a lithium ion secondary battery.
[0017] Solutions for solving problems
[0018] <1> A positive electrode material for a lithium ion secondary battery, comprising aggregated particles, wherein the aggregated particles are formed by aggregating a plurality of primary particles of a positive electrode active material covered with a carbonaceous film,
[0019] The positive electrode active material comprises lithium iron phosphate, wherein the lithium iron phosphate contains lithium (Li), iron (Fe) and a metal element A (A) in a mass ratio of Li:Fe:A=x:y:1-y, wherein x is 0.9<x<1.1, y is 0.2<y≤1.0, and the metal element A is at least one additional element selected from the group consisting of Mg, Zn, Co, Mn, Ni, Ti and V,
[0020] At least one of calcium phosphate (Ca3(PO4)2) particles and aluminum phosphate (AlPO4) particles exists on the surface of primary particles of the positive electrode active material covered with the carbonaceous film, on the grain boundaries between primary particles, or on both the surface and the grain boundaries.
[0021] <2> The positive electrode material for a lithium ion secondary battery according to <1>, wherein a Ca content in the positive electrode material is 100 mass ppm or more and 5000 mass ppm or less, and an Al content in the positive electrode material is 100 mass ppm or more and 5000 mass ppm or less.
[0022] <3> The positive electrode material for a lithium ion secondary battery according to <1> or <2>, wherein the positive electrode material has a crystallite diameter of 80 nm or more and 150 nm or less, and a specific surface area of 6.0 m 2 / g or more and 14.0m 2 / g or less.
[0023] <4> The positive electrode material for a lithium ion secondary battery according to <1> or <2>, wherein the tap density of the positive electrode material is 0.8 g / cm 3 The density of the pressed powder when the positive electrode material is compressed into a circular shape with a diameter of 20 mm under a pressure of 16 kN is 2.4 g / cm 3 above.
[0024] <5> A method for producing a positive electrode material for a lithium ion secondary battery, which is a method for producing the positive electrode material for a lithium ion secondary battery according to <1> or <2>,
[0025] The above method has the following steps:
[0026] A crystallization step, using a metal source having a valence of 2, 3 or both and a phosphoric acid source, to obtain crystallized particles through a crystallization reaction;
[0027] A water washing step, washing and drying the crystallized particles to obtain a precursor of the positive electrode active material;
[0028] a mixing step of mixing the precursor of the positive electrode active material, a lithium source and a carbon source to obtain a raw material mixture; and
[0029] a calcining step of calcining the raw material mixture in a non-oxidizing atmosphere to obtain a positive electrode material containing the positive electrode active material;
[0030] In the above-mentioned crystallization step, one or more selected from the group consisting of a Ca source and an Al source are added to the crystallization so that at least one of calcium phosphate (Ca3(PO4)2) particles and aluminum phosphate (AlPO4) particles is present on the surface of the primary particles of the obtained crystallization particles, on the grain boundaries between the primary particles, or on both the above-mentioned surface and the above-mentioned grain boundaries.
[0031] <6> A positive electrode for a lithium ion secondary battery, comprising: an aluminum current collector, and a positive electrode composite material layer formed on the aluminum current collector,
[0032] The positive electrode composite material layer contains the positive electrode material for lithium ion secondary battery described in <1> or <2>.
[0033] <7> A positive electrode for a lithium ion secondary battery, comprising at least a positive electrode, a negative electrode and an electrolyte,
[0034] The positive electrode is the positive electrode for a lithium ion secondary battery as described in <6>.
[0035] Effects of the Invention
[0036] According to one embodiment of the present invention, a positive electrode material containing lithium iron phosphate having high input-output characteristics when used as a positive electrode of a lithium ion secondary battery, a method for producing the same, a positive electrode for a lithium ion secondary battery, and a lithium ion secondary battery can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 It is a schematic diagram of the cross-sectional structure of the coin-type battery produced in the Example and the Comparative Example. DETAILED DESCRIPTION
[0038] Hereinafter, the mode for implementing the present invention will be described, but the present invention is not limited to the following embodiments, and various modifications and substitutions can be applied to the following embodiments without departing from the scope of the present invention. In addition, in the following description, the description "A to B" means "Above A and Below B".
[0039] [Positive electrode materials for lithium-ion secondary batteries]
[0040] The positive electrode material for lithium ion secondary battery of this embodiment includes aggregated particles, wherein the aggregated particles are formed by aggregating a plurality of primary particles of a positive electrode active material covered with a carbonaceous film.
[0041] The positive electrode active material comprises lithium iron phosphate, wherein the lithium iron phosphate contains lithium (Li), iron (Fe) and a metal element A (A) in a mass ratio of Li:Fe:A=x:y:1-y, wherein x is 0.9<x<1.1, y is 0.2<y≤1.0, and the metal element A is at least one additional element selected from the group consisting of Mg, Zn, Co, Mn, Ni, Ti and V,
[0042] At least one of calcium phosphate (Ca3(PO4)2) particles and aluminum phosphate (AlPO4) particles exists on the surface of primary particles of the positive electrode active material covered with the carbonaceous film, on the grain boundaries between primary particles, or on both the surface and the grain boundaries.
[0043] The positive electrode material for a lithium ion secondary battery of the present embodiment has a structure including lithium iron phosphate as a positive electrode active material and having a conductive carbonaceous coating for improving the conductivity of the positive electrode material.
[0044] Hereinafter, the positive electrode material for lithium ion secondary batteries may be abbreviated as “positive electrode material”. Also, lithium iron phosphate may be abbreviated as “LFP”.
[0045] LFP is synthesized by heating during the production process by calcination, etc. In addition, although LFP may be coated with a carbonaceous film during synthesis, when the carbonaceous film is formed in a separate process, it is necessary to perform heat treatment together with the carbon source.
[0046] LFP has a particle structure composed of secondary particles formed by the aggregation of primary particles. When heated by sintering or heat treatment as described above, even if the growth of primary particles is suppressed by adding additional elements to the primary particles or forming a different phase, the primary particles will sinter, and the primary particles will sinter firmly to form coarse aggregated particles (secondary particles).
[0047] When used as a positive electrode of a lithium ion secondary battery in a state where sintering has progressed, the contact area with the electrolyte cannot be sufficiently obtained, and the distance of electron conduction and lithium (Li) ion conduction in the coarse particles increases, thereby reducing the charge and discharge characteristics of the battery.
[0048] Hereinafter, a lithium ion secondary battery may be simply referred to as a "battery".
[0049] Although there is also a method of mechanically pulverizing and refining after sintering or heat treatment, strong pulverization is required when the primary particles are firmly sintered, which may cause the problem of reduced crystallinity due to pulverization. In addition, when pulverization is performed after the conductive carbonaceous film is formed, it is possible to form a new surface without a conductive carbonaceous film, peel off the film, etc., further resulting in a reduction in the charge and discharge characteristics of the battery.
[0050] The positive electrode material of the present embodiment is in the following state: at least one of calcium phosphate (Ca3(PO4)2) particles and aluminum phosphate (AlPO4) particles exists on the surface of the primary particles of LFP as the positive electrode active material, the grain boundary between the primary particles, or both the surface and the grain boundary. Hereinafter, "at least one of calcium phosphate (Ca3(PO4)2) particles and aluminum phosphate (AlPO4) particles" is sometimes abbreviated as "phosphate particles".
[0051] When phosphoric acid particles are present, they function as pillars during firing, and can delay the progress of sintering of the primary particles, thereby suppressing the formation of coarse particles.
[0052] The phosphoric acid particles only need to be formed on the surface of the primary particles of LFP, the grain boundaries between the primary particles, or a part of the aforementioned surface and the aforementioned grain boundaries, and do not need to be formed on the entire surface and the grain boundaries. In addition, the phosphoric acid particles can be optionally present in a state of being directly present on the surface of the LFP that functions as a positive electrode active material, or in a state of being present on a carbonaceous film that coats the positive electrode active material.
[0053] The phosphoric acid particles are not particularly limited, and at least a portion of the particles may have a diameter of 10 nm to 500 nm, preferably 20 nm to 300 nm. When particles of such a size exist, the sintering of the primary particles can be further delayed, and the formation of coarse particles can be further suppressed.
[0054] On the other hand, if coarse phosphoric acid particles exist, they are concentrated in the secondary particles, and the number of phosphoric acid particles existing on the surface and grain boundaries of the primary particles decreases, which reduces the effect of delaying sintering. Therefore, the maximum diameter of the phosphoric acid particles is preferably 1 μm or less.
[0055] The size of the phosphoric acid particles can be confirmed by observing the surface or cross-section of the LFP particles using a scanning electron microscope, a transmission electron microscope, or the like.
[0056] In the above-mentioned positive electrode material, the Ca content in the positive electrode material is preferably 100 mass ppm to 5000 mass ppm, more preferably 150 mass ppm to 3000 mass ppm, further preferably 200 mass ppm to 2000 mass ppm, and further preferably 450 mass ppm to 2000 mass ppm. In addition, the Al content in the positive electrode material is preferably 100 mass ppm to 5000 mass ppm, more preferably 150 mass ppm to 3000 mass ppm, further preferably 200 mass ppm to 2000 mass ppm, and further preferably 450 mass ppm to 2000 mass ppm. By making the Ca content and Al content in the positive electrode material within the above-mentioned range, a sufficient amount of phosphoric acid particles can be formed on the surface and interface of the primary particles, and the coarse particles formed by the sintering of the primary particles can be suppressed.
[0057] As for Ca and Al, as long as at least a part of their contents are formed into phosphoric acid particles, they may also exist in a state other than forming phosphoric acid particles, such as a state of solid solution in LFP. The contents of Ca and Al may be analyzed, for example, by ICP emission spectroscopy. The total content of Ca and Al is preferably 500 mass ppm or more, more preferably 1000 mass ppm or more, and further preferably 1150 mass ppm or more.
[0058] The positive electrode material of the present embodiment includes aggregated particles in which a plurality of primary particles of a positive electrode active material including LFP having the above-described composition are aggregated.
[0059] LFP may contain at least one selected from the group consisting of Mg, Zn, Co, Mn, Ni, Ti and V as an additive element A. By including the additive element A, the battery characteristics when the positive electrode material is used in a battery can be improved. In addition, by setting the ratio of lithium (Li) to the metal element other than Li, that is, x, to the above range, the crystallinity of the olivine structure can be improved. The composition of the above LFP does not include Ca and Al that form the phosphate particles, but as described above, the additive element A may also contain trace amounts of Ca and Al.
[0060] For the positive electrode material of the present embodiment, the crystallite diameter can be made to be more than 80nm and less than 150nm. By making the crystallite diameter be the above range, the crystallinity can be improved, and the battery characteristics such as charge and discharge characteristics and cycle characteristics can be made sufficient. From the above viewpoint, the crystallite diameter is preferably more than 80nm and less than 130nm, more preferably more than 80nm and less than 120nm, and further preferably more than 80nm and less than 110nm.
[0061] The crystallite diameter can be determined using the Scherrer equation based on the peaks of the X-ray diffraction pattern.
[0062] The specific surface area of the positive electrode material can be 6.0 m 2 / g or more and 14.0m 2 / g or less. As a result, the electrolyte is in full contact with the positive electrode material, which can have high charge and discharge characteristics, and can inhibit the generation of fine particles to increase the packing density in the battery. From the above viewpoints, the specific surface area is preferably 6.5m 2 / g or more and 14.0m 2 / g or less, more preferably 8.0m 2 / g or more and 14.0m 2 / g or less, more preferably 8.7m 2 / g or more and 14.0m 2 / g or less.
[0063] In addition, the tap density of the positive electrode material can be made to be 0.8 g / cm 3 The tap density is an indicator of the filling density in the battery and is set to 0.8 g / cm 3 The tap density is preferably 1.1 g / cm 3 The upper limit of the tap density is not particularly limited, and can be, for example, 3.0 g / cm 3 the following.
[0064] The tap density is preferably 2.0 g / cm 3 Below, more preferably 1.2 g / cm 3 the following.
[0065] In addition, the NMP (N-methyl-2-pyrrolidone) absorption of the above-mentioned positive electrode material can be made to be less than 40mL / 100g. The NMP absorption is an index representing the amount of pores in the positive electrode material. By making the NMP absorption less than 40mL / 100g, the pores can be limited to increase the packing density in the battery. The lower limit of the NMP absorption is not particularly limited, and from the viewpoint of good contact with the electrolyte, it can be set to more than 20mL / 100g. From the above viewpoint, the NMP absorption is preferably more than 26mL / 100g and less than 40mL / 100g, more preferably more than 33mL / 100g and less than 40mL / 100g, and further preferably more than 37mL / 100g and less than 40mL / 100g.
[0066] NMP may be used instead of DBP (dibutyl phthalate) and the NMP absorption may be measured in accordance with JIS K6217-4:2017.
[0067] In addition, the density of the powder compact when the positive electrode material is compressed at a pressure of 16 kN can be 2.4 g / cm 3As a result, a high-density positive electrode can be formed, which can fully increase the charge and discharge capacity per unit volume of the battery. The density of the pressed powder is not particularly limited and can be set to 3.0 g / cm 3 the following.
[0068] The method for measuring the density of the compressed powder body is not particularly limited. For example, a certain amount of sample is placed in a mold with an inner diameter of 20 mm, and a load of 16 kN is applied. The volume of the sample is calculated based on the height measurement value of the sample under the load, and the mass of the sample is divided by the volume to obtain the density of the compressed powder body.
[0069] [Method for producing positive electrode material for lithium ion secondary battery]
[0070] The method for manufacturing the positive electrode material for lithium ion secondary batteries of the present embodiment is a method for manufacturing the positive electrode material for lithium ion secondary batteries of the present embodiment, and the method comprises: a crystallization step, a water washing step, a mixing step, and a sintering step. Hereinafter, the method for manufacturing the positive electrode material for lithium ion secondary batteries of the present embodiment is sometimes referred to as "the present manufacturing method".
[0071] Hereinafter, each step of the present production method will be described, and description of a part that has already been described may be omitted.
[0072] (Crystallization process)
[0073] In the crystallization process, a metal source having a valence of 2, 3 or both and a phosphate source are used to obtain crystallization particles by a crystallization reaction. As crystallization particles, a phosphate metal composite compound can usually be obtained. Moreover, in the crystallization process, one or more selected from the group consisting of a Ca source and an Al source are added to the crystallization, so that at least one of calcium phosphate (Ca3(PO4)2) particles and aluminum phosphate (AlPO4) particles is present on the surface of the primary particles of the obtained crystallization particles, the grain boundaries between the primary particles, or both the surface and the grain boundaries. A portion of Ca and Al can also be dissolved in the crystallization particles.
[0074] The raw material solution in which the metal source and the phosphoric acid source are dissolved and coexist in the form of ions is added to a reaction aqueous solution adjusted to a pH range of 7 to 10 at a liquid temperature of 25°C to cause coprecipitation. Since the raw material solution is acidic, a base is added dropwise to the reaction aqueous solution, and the raw material solution is then added dropwise while maintaining the pH in the above range, thereby obtaining crystallized particles as a coprecipitate.
[0075] A raw material solution containing a metal source and a phosphate source is added dropwise to a reaction aqueous solution controlled to a pH of 7 to 10, preferably 7 to 9, at a liquid temperature of 25°C. This controls the ratio of metal to phosphate and allows crystallization particles of uniform composition to be obtained.
[0076] The ratio of the amount of metal to phosphoric acid in the positive electrode active material, i.e., LFP, obtained by the present manufacturing method is substantially the same as that in the crystallized particles. In addition, the ratio of the amount of metal to phosphorus in the crystallized particles is substantially the same as that in the raw material solution. Therefore, by controlling the composition of the raw material solution, the composition of the target LFP can be controlled. Similar to the composition of the target LFP, the ratio of the amount of iron to phosphoric acid can be set to 1, and considering the influence of the added elements and impurities, it can be set to about 0.9 to 1.1.
[0077] The metal source may be a water-soluble divalent or trivalent metal salt, preferably a sulfate. For example, iron sulfate, magnesium sulfate, zinc sulfate, cobalt sulfate, nickel sulfate, titanium sulfate, vanadium sulfate, etc. may be used as the metal source. In addition, an acid-soluble hydroxide may also be used.
[0078] The metal source may be used alone or in combination of two or more kinds, but it is preferred to use only one kind.
[0079] The phosphoric acid source may be any water-soluble phosphoric acid compound, and preferably orthophosphoric acid (H3PO4), diammonium phosphate (NH4H2PO4), diammonium hydrogen phosphate ((NH4)2HPO4), etc., which have a low risk of impurity contamination, can be used.
[0080] The phosphoric acid source may be used alone or in combination of two or more. However, it is preferred to use only one kind.
[0081] When preparing the raw material solution, in order to adjust the valence of the metal source in the raw material solution, an oxidant such as a hydrogen peroxide (H2O2) aqueous solution may be added to the reaction aqueous solution. The amount of the oxidant added is not particularly limited and may be set in the range of 0.3 to 3.0 times the amount of the metal source.
[0082] The oxidizing agent may be used alone or in combination of two or more.
[0083] When adjusting the pH of the reaction aqueous solution, one or more selected from the group consisting of sodium hydroxide and lithium hydroxide can be used as an alkali source.
[0084] The alkali source may be used alone or in combination of two or more.
[0085] The complexing agent may be added to the aqueous reaction solution together with the alkali source. The complexing agent is not particularly limited as long as it can form a complex by bonding with iron ions, other metal ions, etc. in aqueous solution, and an example thereof is an ammonium ion donor.
[0086] The complexing agent may be used alone or in combination of two or more.
[0087] The ammonium ion donor is not particularly limited, and for example, ammonia, ammonium sulfate, ammonium chloride, ammonium carbonate, ammonium fluoride, etc. The ammonium ion concentration in the reaction aqueous solution can be in the range of 3 g / L to 25 g / L.
[0088] The ammonium ion donor may be used alone or in combination of two or more.
[0089] Alternatively, the alkali source and the complexing agent may be mixed and added to the aqueous reaction solution in the form of a buffer solution.
[0090] In the crystallization step, a Ca source, an Al source, or both a Ca source and an Al source are added to the reaction aqueous solution. Thus, at least one of calcium phosphate (Ca3(PO4)2) particles and aluminum phosphate (AlPO4) particles can be present on the surface of primary particles of the obtained crystallization particles, on the grain boundaries between primary particles, or on both the aforementioned surface and the aforementioned grain boundaries.
[0091] The Ca source may be added to the reaction aqueous solution alone in the form of an aqueous solution, or may be added to the raw material solution. In this case, calcium hydroxide or the like may be used as the Ca source. In the case where Ca is contained in the phosphate source or the metal source in the form of impurities or the like, the Ca contained in the phosphate source or the metal source may also be used. That is, the method of adding the Ca source is not limited, and the Ca source may be contained in the crystallization particles in a desired amount, for example, in a manner such that the Ca content in the target LFP reaches 100 mass ppm to 5000 mass ppm.
[0092] Similar to the Ca source, the method of adding the Al source is not limited, and the Al source may be contained in the crystallized particles in a desired amount, for example, so that the Al content in the target LFP becomes 100 to 5000 mass ppm.
[0093] As the Al source, aluminum hydroxide, aluminum sulfate, sodium aluminate, etc. can be used.
[0094] The Ca source and the Al source may be used independently of each other, or two or more of them may be used as a mixture.
[0095] (Water washing process)
[0096] In the water washing step, the crystallized particles obtained in the crystallization step are washed with water and dried to obtain the precursor of the positive electrode active material.
[0097] Hereinafter, the precursor of the positive electrode active material may be simply referred to as “precursor”.
[0098] The water washing can be carried out by any conventional method as long as the impurities can be reduced. For example, the crystallized particles can be mixed with any of pure water, distilled water and ion exchange water without the risk of being mixed with impurities, stirred, and then washed with water by solid-liquid separation.
[0099] The drying is not particularly limited, and the crystallized particles may be dried in a non-oxidizing atmosphere such as a vacuum atmosphere or an inert gas atmosphere from the viewpoint of preventing oxidation of the crystallized particles.
[0100] The composition of the target positive electrode active material inherits the composition ratio of the metal elements and phosphoric acid of the precursor obtained in the water washing process, so the mixing ratio of the metal source and the phosphoric acid source used in the crystallization process can be determined in a manner to achieve the target composition. Specifically, for example, it is preferred that the ratio of Fe:A:PO4=y:1-y:1+α contains iron (Fe), element A (A), and phosphoric acid (PO4), wherein y is 0.2<y≤1.0, α is -0.1≤α≤0.1, and element A is at least one added element selected from the group consisting of Mg, Zn, Co, Mn, Ni, Ti and V. In addition, at least one of calcium phosphate (Ca3(PO4)2) particles and aluminum phosphate (AlPO4) particles exists on the surface of the primary particles of the precursor, the grain boundaries between the primary particles, or both the aforementioned surface and the aforementioned grain boundaries. Part of Ca and Al may also be dissolved in the precursor.
[0101] The aforementioned precursor can also be expressed as the general formula Fe y A 1-y (PO4) 1+α . y, α, and the element M in the formula have been explained, so the explanation is omitted here.
[0102] (Mixing process)
[0103] In the mixing step, the precursor of the positive electrode active material obtained in the water washing step, the lithium source, and the carbon source are mixed to obtain a raw material mixture.
[0104] The precursor and the lithium source are preferably mixed so that the ratio x (Li / Me) of the number of atoms of lithium (Li) to the number of atoms of metal other than lithium (Me) in the obtained LFP is greater than 0.9 and less than 1.1.
[0105] Since x is almost unchanged before and after the calcination step described later, x in the raw material mixture supplied to the calcination step is substantially the same as Li / Me in the obtained LFP. Therefore, in the mixing step, it is preferred to mix so that the obtained LFP has the target x.
[0106] In the firing process, x may decrease slightly due to volatilization of lithium, etc. Therefore, it is preferred that x in the mixing process is higher than x of the target LFP by the amount of decrease in x. The amount of decrease in x is approximately constant due to the firing conditions, and can therefore be easily determined by preliminary tests, etc.
[0107] The lithium source is not particularly limited, and lithium carbonate, lithium hydroxide, lithium sulfate, etc. can be used. Lithium carbonate and lithium hydroxide free of impurities can be preferably used.
[0108] The lithium source may be used alone or in combination of two or more. However, it is preferred to use only one type.
[0109] Examples of the carbon source include: graphite such as natural graphite and artificial graphite; carbon black such as acetylene black and Ketjen black; carbon fiber, sucrose, ascorbic acid and other organic compounds that decompose to produce carbonaceous materials, and one or more of them can be used.
[0110] The carbon source may be used alone or in combination of two or more.
[0111] The amount of the carbon source to be mixed is not particularly limited as long as it is an amount that allows the LFP to be coated with the conductive carbonaceous film. The amount of carbon to be mixed is 1 to 5% by mass relative to the LFP.
[0112] As a mixing means for mixing the precursor and the lithium compound in the mixing step, a general mixer can be used, for example, a swing mixer, a Loedige mixer, a Julia mixer, a V-type blender, etc. can be used.
[0113] (Firing process)
[0114] In the calcining step, the raw material mixture obtained in the mixing step is calcined in a non-oxidizing atmosphere to obtain a positive electrode material containing a positive electrode active material.
[0115] In the firing step, the firing temperature for firing the raw material mixture, that is, the maximum temperature set in the firing furnace is not particularly limited, but is preferably 600°C to 850°C, and more preferably 600°C to 750°C, for example.
[0116] By setting the sintering temperature to 600°C or above, lithium can be fully diffused into the precursor, and the crystal structure of the obtained LFP can be made particularly uniform, which can fully improve the battery characteristics when used as a positive electrode active material. In addition, since the reaction between the lithium source and the precursor can be fully carried out, the remaining lithium residue or the unreacted precursor particle residue can be further suppressed.
[0117] The holding time at the calcination temperature can be set to, for example, 0.5 to 12 hours, and preferably 2 to 6 hours.
[0118] In the present production method, the phosphoric acid particles exist on the surface and grain boundaries of the primary particles of the precursor, and do not react with the lithium source etc. even during sintering, and exist as phosphoric acid particles. Therefore, the phosphoric acid particles can delay the sintering of the primary particles and inhibit the formation of coarse particles.
[0119] The holding time at the firing temperature is not particularly limited, and may be set to the general conditions for firing LFP.
[0120] The atmosphere during firing is not particularly limited as long as it is a non-oxidizing atmosphere, and for example, an inert atmosphere such as nitrogen or a reducing atmosphere may be used.
[0121] Here, the atmosphere during firing is an atmosphere excluding gases generated by reactions during firing, and may be, for example, an atmosphere gas supplied to a firing furnace.
[0122] In the firing step, the pre-firing may be performed at a temperature lower than the firing temperature. The pre-firing temperature may be, for example, 350°C to 550°C, and preferably 400°C to 500°C.
[0123] The holding time at the calcination temperature can be set to, for example, 0.5 to 12 hours, and preferably 2 to 6 hours.
[0124] After the pre-firing, the material may be cooled before being subjected to the firing step, or the temperature may be raised from the pre-firing temperature to the firing temperature to continuously perform the firing step.
[0125] The atmosphere during the preliminary firing is not particularly limited, and for example, the same atmosphere as that in the firing step may be used.
[0126] The firing furnace is not particularly limited, and the raw material mixture may be fired, for example, in an inert atmosphere or a reducing atmosphere. From the viewpoint of maintaining a uniform atmosphere in the furnace, an electric furnace without gas generation is preferred, and an intermittent or continuous furnace may be used as desired. In addition, a furnace in which the raw material mixture is filled into a firing container and fired, or a furnace in which the raw material mixture is flowed and fired may be used as desired. However, from the viewpoint of particularly improving productivity, a continuous firing furnace is preferably used in the firing process.
[0127] (Crushing process)
[0128] The powder of the positive electrode material obtained through the calcining step may sometimes aggregate or lightly sinter. In this case, the present production method may optionally include a crushing step of crushing the powder after the calcining step.
[0129] Here, crushing refers to the following operation: mechanical energy is applied to an aggregate composed of multiple secondary particles generated by sintering necking between secondary particles during firing, and the secondary particles are separated without almost destroying the secondary particles themselves, thereby dissolving the aggregate. In the crushing process, it is preferred to select the crushing conditions so that the average particle size, particle size distribution, etc. of the positive electrode material after crushing reach the desired range, and implement it. After crushing, sieving can also be performed as needed.
[0130] (About the composition of positive electrode materials)
[0131] The composition of the positive electrode material produced by the above-described production method is not particularly limited. The positive electrode material includes a positive electrode active material, the positive electrode active material includes aggregated particles, and the aggregated particles are formed by aggregating a plurality of primary particles covered with a carbonaceous film.
[0132] At least one of calcium phosphate (Ca3(PO4)2) particles and aluminum phosphate (AlPO4) particles exists on the surface of primary particles of LFP contained in the positive electrode active material, on the grain boundaries between primary particles, or on both the surface and the grain boundaries.
[0133] The composition of the LFP may contain lithium (Li), iron (Fe), element A (A), and phosphoric acid (PO4) in a ratio of Li:Fe:A:PO4=x:y:1-y:1+β, for example. As for the above x, y, and β, it is preferred that x is 0.9<x<1.1, y is 0.2<y≤1.0, and β is -0.1≤β≤0.1. Element A may be at least one additional element selected from the group consisting of Mg, Zn, Co, Mn, Ni, Ti, and V. In addition, a portion of Ca and Al may be dissolved in the LFP.
[0134] The positive electrode active material can also be expressed as the general formula Li x Fe y A 1-y (PO4) 1+β The x, y, β and element A in the formula have been explained, and therefore, the explanation is omitted here.
[0135] According to the present production method described above, it is possible to provide a positive electrode material containing lithium iron phosphate having high input-output characteristics when used as a positive electrode of a lithium ion secondary battery.
[0136] [Positive electrode for lithium-ion secondary battery]
[0137] The positive electrode for lithium ion secondary battery of this embodiment comprises: an aluminum current collector and a positive electrode composite material layer formed on the aluminum current collector.
[0138] The positive electrode mixture layer contains the positive electrode material for lithium ion secondary battery of the present embodiment.
[0139] The positive electrode is a sheet-like member, and is formed, for example, by applying a positive electrode composite material paste containing the above-described positive electrode material as a positive electrode active material on the surface of an aluminum foil current collector (aluminum current collector) and drying the paste.
[0140] It should be noted that the positive electrode is appropriately processed according to the battery used, for example, cutting processing to form it into an appropriate size according to the target secondary battery, and pressurizing and compressing processing such as roller pressing to increase the electrode density.
[0141] A solvent is added to the positive electrode composite material and kneaded to form a positive electrode composite material paste. The positive electrode composite material is formed by mixing the above-mentioned positive electrode material in powder form, a conductive material, and a binder.
[0142] The conductive material is added to impart appropriate conductivity to the electrode. The conductive material is not particularly limited, and examples thereof include graphite (natural graphite, artificial graphite, expanded graphite, etc.), carbon black materials such as acetylene black and Ketjen Black (registered trademark), and the like.
[0143] The conductive material may be used alone or in combination of two or more.
[0144] The binder plays a role of binding the positive electrode active material particles. The binder used in the positive electrode composite material is not particularly limited, and for example, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), fluorine rubber, ethylene propylene diene rubber, styrene-butadiene, cellulose resin, polyacrylic acid, etc. can be used.
[0145] The binder may be used alone or in combination of two or more.
[0146] It should be noted that activated carbon or the like may also be added to the positive electrode composite material. By adding activated carbon or the like to the positive electrode composite material, the double layer capacity of the positive electrode can be increased.
[0147] The solvent is a substance that dissolves the binder and disperses the positive electrode active material, the conductive material, the activated carbon, etc. in the binder. The solvent is not particularly limited, and for example, an organic solvent such as N-methyl-2-pyrrolidone can be used.
[0148] The solvent may be used alone or in combination of two or more.
[0149] In addition, the mixing ratio of each substance in the positive electrode composite material paste is not particularly limited. For example, when the solid content of the positive electrode composite material other than the solvent is set to 100 parts by mass, the content of the positive electrode active material can be 60 parts by mass to 98 parts by mass, the content of the conductive material is 1 part by mass to 20 parts by mass, and the content of the binder is 1 part by mass to 20 parts by mass, as in the positive electrode of a general lithium ion secondary battery.
[0150] [Lithium-ion secondary battery]
[0151] In the lithium ion secondary battery of the present embodiment, the positive electrode may include the positive electrode material of the present embodiment described above. Hereinafter, a configuration example of the battery of the present embodiment will be described for each component.
[0152] The battery of this embodiment has substantially the same structure as a general lithium ion secondary battery except that a positive electrode material, more specifically, a positive electrode material obtained by the above-described method for producing a positive electrode material for a lithium ion secondary battery is used as a positive electrode active material.
[0153] Specifically, the battery of the present embodiment has the following structure: a housing, a positive electrode, a negative electrode, a non-aqueous electrolyte housed in the housing, and a separator as needed. More specifically, for example, when a non-aqueous electrolyte is used, the positive electrode and the negative electrode are stacked with a separator to form an electrode body, the obtained electrode body is immersed in the non-aqueous electrolyte, and a collector lead is used to connect the positive electrode collector of the positive electrode and the positive terminal connected to the outside, and the negative electrode collector of the negative electrode and the negative terminal connected to the outside, respectively, and sealed in the housing, thereby forming the secondary battery of the present embodiment.
[0154] It should be noted that the structure of the secondary battery of this embodiment is obviously not limited to the above example, and its outer shape may also adopt various shapes such as cylindrical shape, laminated shape, etc. The positive electrode has been described above, so the description thereof is omitted.
[0155] (negative electrode)
[0156] The negative electrode is a sheet-like member formed by applying a negative electrode composite material paste on the surface of a metal foil collector such as copper and drying it. Although the components or compatibility of the negative electrode composite material paste, the raw materials of the collector, etc. are different, the negative electrode is essentially formed by the same method as the positive electrode, and can be processed in various ways as needed, just like the positive electrode.
[0157] The negative electrode composite material paste is a material prepared by adding an appropriate solvent to a negative electrode composite material obtained by mixing a negative electrode active material and a binder to form a paste.
[0158] The negative electrode active material may be, for example: a lithium-containing material such as metallic lithium and a lithium alloy; or an occlusion material that can occlude and release lithium ions.
[0159] The storage material is not particularly limited, and for example, natural graphite, artificial graphite, phenolic resin and other organic compound sintered bodies, and powders of carbon materials such as coke can be used. When the negative electrode active material adopts the storage material, as with the positive electrode, a fluorine-containing resin such as PVDF can be used as a binder, and an organic solvent such as N-methyl-2-pyrrolidone can be used as a solvent for dispersing the negative electrode active material in the binder.
[0160] (Separator)
[0161] When a non-aqueous electrolyte is used, the separator is arranged in a manner sandwiched between the positive electrode and the negative electrode, and has the function of separating the positive electrode from the negative electrode and retaining the electrolyte. The separator can be, for example, a thin film having multiple micropores such as polyethylene or polypropylene, and is not particularly limited as long as it has the above-mentioned function.
[0162] (Non-aqueous electrolyte)
[0163] As the non-aqueous electrolyte, for example, a non-aqueous electrolyte solution can be used.
[0164] As a non-aqueous electrolyte, for example, a substance obtained by dissolving a lithium salt as a supporting salt in an organic solvent can be used. In addition, as a non-aqueous electrolyte, a substance in which a lithium salt is dissolved in an ionic liquid can also be used. It should be noted that an ionic liquid refers to a salt composed of cations and anions other than lithium ions and is liquid at room temperature (25°C).
[0165] As the organic solvent, there can be used: cyclic carbonates such as ethylene carbonate, propylene carbonate, butylene carbonate and trifluoropropylene carbonate; chain carbonates such as diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate and dipropyl carbonate; ether compounds such as tetrahydrofuran, 2-methyltetrahydrofuran and dimethoxyethane; sulfur compounds such as ethyl methyl sulfone and butane sultone; phosphorus compounds such as triethyl phosphate and trioctyl phosphate, etc.
[0166] The organic solvent may be used alone or in combination of two or more kinds thereof.
[0167] As supporting salts, LiPF6, LiBF4, LiClO4, LiAsF6, LiN(CF3SO2)2, and complex salts thereof can be used. In addition, the non-aqueous electrolyte can also contain a radical scavenger, a surfactant, a flame retardant, and the like.
[0168] The supporting salt may be used alone or in combination of two or more.
[0169] In addition, a solid electrolyte may be used as a non-aqueous electrolyte. A solid electrolyte has the property of being able to withstand a high voltage. Examples of the solid electrolyte include inorganic solid electrolytes and organic solid electrolytes.
[0170] Examples of the inorganic solid electrolyte include oxide-based solid electrolytes and sulfide-based solid electrolytes.
[0171] The oxide-based solid electrolyte is not particularly limited, and for example, a substance containing oxygen (O) and having lithium ion conductivity and electronic insulation can be preferably used. Specifically, examples of the oxide-based solid electrolyte include lithium phosphate (Li3PO4), Li3PO4N X 、LiBO2N X , LiNbO3, LiTaO3, Li2SiO3, Li4SiO4-Li3PO4, Li4SiO4-Li3VO4, Li2O-B2O3-P2O5, Li2O-SiO2, Li2O-B2O3-ZnO, Li 1+X Al X Ti 2-X (PO4)3(0≤X≤1), Li 1+X Al X Ge 2-X (PO4)3(0≤X≤1), LiTi2(PO4)3, Li 3X La 2 / 3-X TiO3(0≤X≤2 / 3), Li5La3Ta2O 12 、Li7La3Zr2O 12 、Li6BaLa2Ta2O 12 , Li 3.6 Si 0.6 P 0.4 O4, etc. As the oxide-based solid electrolyte, one or more selected from these can be used.
[0172] As sulfide-based solid electrolytes, there are no particular limitations, and for example, substances containing sulfur (S) and having lithium ion conductivity and electronic insulation can be preferably used. Specifically, as sulfide-based solid electrolytes, for example, there can be mentioned: Li2S-P2S5, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2S-B2S3, Li3PO4-Li2S-Si2S, Li3PO4-Li2S-SiS2, LiPO4-Li2S-SiS, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, etc. The sulfide-based solid electrolyte can use one or more selected from these.
[0173] It should be noted that as the inorganic solid electrolyte, substances other than those listed above may be used, for example, Li 3 N, LiI, Li 3 N—LiI—LiOH, etc. may be used.
[0174] The organic solid electrolyte is not particularly limited as long as it is a polymer compound showing ion conductivity, and examples thereof include polyethylene oxide, polypropylene oxide, and copolymers thereof. The organic solid electrolyte may also contain a supporting salt (lithium salt).
[0175] Only one kind of organic solid electrolyte may be used, or two or more kinds of organic solid electrolyte may be used.
[0176] (Shape and structure of secondary battery)
[0177] As described above, the battery of the present embodiment can be made into various shapes such as cylindrical and stacked. Regardless of the shape, in the case where the secondary battery of the present embodiment uses a non-aqueous electrolyte as a non-aqueous electrolyte, the positive electrode and the negative electrode are stacked across a separator to form an electrode body. The following structure can be made: the obtained electrode body is immersed in a non-aqueous electrolyte, and a collector lead is used to connect the positive electrode collector and the positive terminal connected to the outside, and the negative electrode collector and the negative terminal connected to the outside, and sealed in a battery case.
[0178] It should be noted that the battery of the present embodiment is not limited to the mode of using non-aqueous electrolyte as non-aqueous electrolyte, for example, a secondary battery using solid non-aqueous electrolyte, i.e., an all-solid-state battery, can also be made. In the case of making an all-solid-state battery, the composition other than the positive electrode material can be appropriately changed as needed.
[0179] As mentioned above, the battery of the present embodiment uses the positive electrode material of the present embodiment as the material of the positive electrode, so the battery capacity and input-output characteristics are excellent. Therefore, the battery of the present embodiment can be preferably used as a rechargeable battery for clean energy vehicles such as portable information terminals such as portable phones, smart phones, tablet computers, notebook personal computers, portable music players, digital cameras, medical equipment, HEV (Hybrid Electric Vehicle), EV (Electric Vehicle), PHEV (Plug-in Hybrid Electric Vehicle), etc.
[0180] Example
[0181] Hereinafter, the present embodiment will be described in more detail with reference to examples. However, the present embodiment is not limited to the following examples.
[0182] 1. About the evaluation method
[0183] In the following Examples and Comparative Examples, evaluation was performed by the following methods.
[0184] (1) Composition analysis: The composition of the positive electrode material was measured by ICP emission spectrometry.
[0185] (2) Crystallite diameter of positive electrode material: A diffraction pattern was measured using an X-ray diffractometer under the following measurement conditions.
[0186] Radiation source: Cu-Kα
[0187] Step size: 0.01° / step
[0188] Scan speed: 3 seconds / step
[0189] In the measured diffraction pattern, the crystallite diameter was calculated from the following formulae (i) and (ii) using the half value width (B) of the peak in the range of 2θ of 28.8 to 30.8°.
[0190] Crystallite diameter (nm) = {0.9 × 1.5418 × 0.1} / {β × COS (〔29.78 / 2〕 × π / 2)} (i)
[0191] β=(Bb) (ii)
[0192] Wherein, B is the half-value width of the peak in the range of 2θ of 28.8 to 30.8° in the diffraction pattern measured for the positive electrode active material particles, and b is the half-value width of the reference sample Si (2θ=47.3°).
[0193] (3) Specific surface area: The specific surface area of the positive electrode material was determined by the BET single-point method based on nitrogen adsorption.
[0194] (4) Tap density: The tap density of the positive electrode material was measured by shaking a sample container containing the positive electrode material 500 times using a tapping machine (KRS-409, manufactured by Kuramochi Scientific Instruments Mfg. Co., Ltd.).
[0195] (5) NMP absorption amount of positive electrode material: NMP was used instead of DBP (dibutyl phthalate) and the measurement was performed in accordance with JIS K6217-4:2017.
[0196] (6) Density of compressed powder of positive electrode material: 3 g of sample was placed in a mold with an inner diameter of 20 mm, and the mold was vibrated several times to make the sample surface flat. A preload of 10 kN was applied to the mold three times and then released, and then a load of 16 kN was further applied to the mold. Based on the height measurement values of the sample under the applied load state and the unloaded state, the volume of the sample was calculated, and the compression density when pressurized and depressurized was calculated respectively.
[0197] (7) Production of evaluation batteries and evaluation of battery characteristics
[0198] A coin-type secondary battery 10 for evaluation was prepared (see Figure 1 ), and the battery characteristics (load characteristics and DC resistance) were evaluated. The method for manufacturing the coin-type secondary battery 10 and the method for evaluating the battery characteristics are as follows.
[0199] (Production of positive electrode)
[0200] The positive electrode material, polyvinylidene fluoride (PVdF) as a binder, and acetylene black (AB) as a conductive additive were mixed so that the mass ratio reached positive electrode material: PVdF: AB = 90:5:5 to obtain a mixture. Then, N-methyl-2-pyrrolidone (NMP) as a solvent was added to the mixture to give fluidity, thereby preparing a slurry.
[0201] Next, the slurry was coated on an aluminum (Al) foil (current collector) having a thickness of 30 μm and vacuum dried at 120°C for 12 hours. Subsequently, the slurry was cut into strips having a coating width of 35 mm and repeatedly pressed twice with a roller press at a roller gap of 5 μm and a roller feed speed of 0.5 m / min to produce the positive electrodes of the examples and comparative examples.
[0202] (Manufacturing of lithium-ion secondary batteries)
[0203] like Figure 1 As shown, the coin-type secondary battery 10 is composed of a case 11 and an electrode 12 housed in the case 11 .
[0204] The housing 11 includes a positive electrode can 111 which is hollow and opened at one end, and a negative electrode can 112 which is arranged at the opening of the positive electrode can 111 , and is configured in the following manner: the negative electrode can 112 is arranged at the opening of the positive electrode can 111 , so that a space for storing the electrode 12 is formed between the negative electrode can 112 and the positive electrode can 111 .
[0205] The electrode 12 includes a positive electrode 121 , a separator 122 , and a negative electrode 123 , which are stacked in order and housed in the case 11 such that the positive electrode 121 contacts the inner surface of the positive electrode can 111 , and the negative electrode 123 contacts the inner surface of the negative electrode can 112 .
[0206] It should be noted that the housing 11 includes a gasket 113, which is used to restrict and fix relative movement so that the positive electrode can 111 and the negative electrode can 112 maintain a non-contact state, that is, an electrically insulating state. In addition, the gasket 113 also has the function of sealing the gap between the positive electrode can 111 and the negative electrode can 112 to provide an airtight and liquid-tight barrier between the inside and outside of the housing 11.
[0207] The coin-type secondary battery 10 is produced in the following manner.
[0208] First, the obtained positive electrode was punched into 2 cm 2The positive electrode 121 is made by punching out a lithium metal plate in the same manner as the positive electrode 121 to make the negative electrode 123.
[0209] Next, in a glove box of Ar gas atmosphere with a dew point controlled at -80°C, a separator 122 made of porous polypropylene with a thickness of 25 μm was sandwiched between the positive electrode and the negative electrode and arranged in a coin cell container 11 with a diameter of 2 cm and a thickness of 3.2 mm.
[0210] Then, LiPF6 was added at a concentration of 1 mol / dm 3 The electrolyte is dissolved in a solution of ethylene carbonate (EC) and diethyl carbonate (DEC) in a ratio of EC:DEC=50:50 (volume %) as an electrolyte, and the electrolyte is injected into a coin battery unit container 11 and sealed to produce a lithium ion secondary battery (coin-type secondary battery 10) for battery characteristic evaluation.
[0211] (Evaluation of lithium-ion secondary batteries)
[0212] The obtained coin-type secondary battery 10 was evaluated by the following method.
[0213] (Load characteristics (discharge capacity ratio))
[0214] For the charge and discharge test of the coin-type secondary battery 10, charge and discharge were repeated three times at room temperature (25°C) with a cut-off voltage of 2.0V to 4.1V and a constant current of 0.1C, and the third discharge capacity was set to a discharge capacity of 0.1C. Next, charge was performed at a cut-off voltage of 2.0V to 4.1V and 0.1C, and discharge was performed at 3C.
[0215] The ratio of the measured 3C discharge capacity to the 0.1C discharge capacity was used as the load characteristic and calculated using the following formula (2).
[0216] Load characteristics (%) = (3C discharge capacity / 0.1C discharge capacity) × 100... (2)
[0217] (Direct Current Resistance (DCR))
[0218] At room temperature (25°C), the depth of charge (SOC) of the coin-type battery 10 was adjusted to 50% at a charging rate of 0.1C, and the charging side and the discharging side were alternately energized for 10 seconds at rates of 1C, 3C, 5C, and 10C, and the current value after 10 seconds at each rate was plotted on the horizontal axis, and the voltage value was plotted on the vertical axis. The slope of the approximate straight line obtained based on the least squares method was used as "charging side = input DCR" and "discharging side = output DCR". A 10-minute stop time was set when changing the power direction and the power current at each current.
[0219] [Example 1]
[0220] (Preparation of Precursor of Positive Electrode Active Material)
[0221] 279g of FeSO4·7H2O as an Fe source was dissolved in pure water. 131g of H3PO4 (75% aqueous solution) as a P source and 0.42g of Ca(OH)2 were mixed and dissolved therein. Next, 170g of H2O2 (30W / V% aqueous solution) as an oxidant and pure water for concentration adjustment were added to the mixed aqueous solution to prepare a raw material solution. In addition, sodium hydroxide (30% aqueous solution by mass) and ammonia water (28% aqueous solution by mass) were mixed at a molar ratio of 1:1 to prepare a buffer solution.
[0222] Next, pure water was added to a reaction container equipped with a stirrer and a pH sensor, and the buffer solution and the raw material aqueous solution were added while stirring so that the pH of the reaction aqueous solution in the container reached a range of 8.0 to 8.5 at 25° C. After all the prepared raw material solutions were added, stirring was continued for 30 minutes to allow the reaction to proceed completely.
[0223] After the reaction was completed, the reaction aqueous solution was filtered and washed with distilled water several times to obtain filter cake-like crystal particles, which were vacuum dried at 50° C. for 24 hours to obtain a precursor powder (FePO4) of the positive electrode active material.
[0224] The obtained precursor was observed with a scanning electron microscope, and it was confirmed that it was composed of secondary particles formed by aggregation of primary particles of FePO4, and fine Ca3(PO4)2 particles of 10nm to 300nm existed on the particle surfaces of the primary particles.
[0225] (Production and evaluation of positive electrode materials)
[0226] The obtained precursor powder was mixed with lithium hydroxide (LiOH) as a Li source so that the mass ratio of Li to Fe was Li / Fe = 1.02. Furthermore, 2.5 mass % of sucrose powder was mixed with respect to the synthesized positive electrode material in terms of carbon content to obtain a raw material mixture.
[0227] Next, the obtained raw material mixture was heat treated at 700° C. for 5 hours in a nitrogen atmosphere to synthesize a positive electrode active material and load carbon on the surface of the positive electrode active material particles, thereby producing a positive electrode material for a lithium ion secondary battery of Example 1.
[0228] X-ray diffraction analysis confirmed that the obtained positive electrode material generated LFP as a positive electrode active material. In addition, the obtained positive electrode material was observed with a scanning electron microscope and confirmed that it was composed of a positive electrode active material, which contained secondary particles formed by aggregation of primary particles of LFP, and fine calcium phosphate (Ca3(PO4)2) particles of 10nm to 300nm were maintained from the precursor and existed on the particle surface of the primary particles.
[0229] In addition, it was confirmed that the composition of the obtained positive electrode material was Li:Fe:PO4=1.02:1:1 in terms of the mass ratio.
[0230] [Example 2]
[0231] The positive electrode material for lithium ion secondary battery of Example 2 was prepared and evaluated in the same manner as in Example 1 except that 0.65 g of Al(OH) 3 was mixed instead of Ca(OH) 2 when preparing the precursor of the positive electrode active material.
[0232] X-ray diffraction analysis confirmed that the obtained positive electrode material generated LFP as a positive electrode active material. In addition, the obtained positive electrode material was observed with a scanning electron microscope and confirmed that it was composed of a positive electrode active material, which contained secondary particles formed by aggregation of primary particles of LFP, and fine aluminum phosphate (AlPO4) particles of 10nm to 400nm were maintained from the precursor and existed on the particle surface of the primary particles.
[0233] In addition, it was confirmed that the composition of the obtained positive electrode material was Li:Fe:PO4=1.02:1:1 in terms of the mass ratio.
[0234] [Example 3]
[0235] The positive electrode material for lithium ion secondary battery of Example 3 was prepared and evaluated in the same manner as in Example 1 except that 0.14 g of Ca(OH) 2 and 0.22 g of Al(OH) 3 were mixed when preparing the precursor of the positive electrode active material.
[0236] X-ray diffraction analysis confirmed that the obtained positive electrode material generated LFP as a positive electrode active material. In addition, the obtained positive electrode material was observed with a scanning electron microscope and confirmed that it was composed of a positive electrode active material, which contained secondary particles formed by aggregation of primary particles of LFP, and fine calcium phosphate (Ca3(PO4)2) particles and aluminum phosphate (AlPO4) particles of 10nm to 350nm were maintained from the precursor and existed on the particle surface of the primary particles.
[0237] In addition, it was confirmed that the composition of the obtained positive electrode material was Li:Fe:PO4=1.02:1:1 in terms of the mass ratio.
[0238] [Example 4]
[0239] A positive electrode material for a lithium ion secondary battery of Example 4 was prepared in the same manner as in Example 1 except that 0.70 g of Ca(OH) 2 was mixed when preparing the precursor of the positive electrode active material, and was evaluated.
[0240] X-ray diffraction analysis confirmed that the obtained positive electrode material generated LFP as a positive electrode active material. In addition, the obtained positive electrode material was observed with a scanning electron microscope and confirmed that it was composed of a positive electrode active material, which contained secondary particles formed by aggregation of primary particles of LFP, and fine calcium phosphate (Ca3(PO4)2) particles of 10nm to 400nm were maintained from the precursor and existed on the particle surface of the primary particles.
[0241] In addition, it was confirmed that the composition of the obtained positive electrode material was Li:Fe:PO4=1.02:1:1 in terms of the mass ratio.
[0242] [Example 5]
[0243] The positive electrode material for lithium ion secondary battery of Example 5 was prepared and evaluated in the same manner as in Example 1 except that 0.42 g of Ca(OH) 2 and 0.22 g of Al(OH) 3 were mixed when preparing the precursor of the positive electrode active material.
[0244] X-ray diffraction analysis confirmed that the obtained positive electrode material generated LFP as a positive electrode active material. In addition, the obtained positive electrode material was observed with a scanning electron microscope and confirmed that it was composed of a positive electrode active material, which contained secondary particles formed by aggregation of primary particles of LFP, and fine calcium phosphate (Ca3(PO4)2) particles and aluminum phosphate (AlPO4) particles of 10nm to 400nm were maintained from the precursor and existed on the particle surface of the primary particles.
[0245] In addition, it was confirmed that the composition of the obtained positive electrode material was Li:Fe:PO4=1.02:1:1 in terms of the mass ratio.
[0246] [Comparative Example 1]
[0247] A positive electrode material for a lithium ion secondary battery of Comparative Example 1 was prepared and evaluated in the same manner as in Example 1 except that Ca(OH) 2 was not mixed when preparing the precursor of the positive electrode active material.
[0248] X-ray diffraction analysis confirmed that the obtained positive electrode material produced LFP as a positive electrode active material. In addition, observation of the obtained positive electrode material using a scanning electron microscope revealed that the positive electrode material was composed of a positive electrode active material including secondary particles formed by aggregation of primary particles of LFP.
[0249] In addition, it was confirmed that the composition of the obtained positive electrode material was Li:Fe:PO4=1.02:1:1 in terms of the mass ratio.
[0250] [Table 1]
[0251]
[0252] As shown in Table 1, it was confirmed that the load characteristics and DC resistance in Examples 1 to 5 were better than those in Comparative Example 1. In Comparative Example 1, there were no fine calcium phosphate (Ca3(PO4)2) particles and aluminum phosphate (AlPO4) particles, and the specific surface area was lower than that in Examples 1 to 5, indicating that primary particles were sintered. As described above, it was confirmed that the positive electrode material and the manufacturing method of the present embodiment can provide a positive electrode material containing lithium iron phosphate having high input-output characteristics when used as a positive electrode of a lithium ion secondary battery.
[0253] Description of Reference Numerals
[0254] 10 Coin-type secondary battery
[0255] 11 Shell
[0256] 111 positive electrode tank
[0257] 112 Negative electrode tank
[0258] 113 Gasket
[0259] 12 electrodes
[0260] 121 Positive electrode
[0261] 122 Divider
[0262] 123 Negative electrode
Claims
1. A positive electrode material for a lithium ion secondary battery, comprising aggregated particles, wherein the aggregated particles are formed by aggregating a plurality of primary particles of a positive electrode active material covered with a carbonaceous film, The positive electrode active material comprises lithium iron phosphate, which contains lithium (Li), iron (Fe) and metal element A (A) in a mass ratio of Li:Fe:A=x:y:1-y, wherein: x is 0.9<x<1.1, y is 0.2<y≤1.0, the metal element A is at least one additional element selected from the group consisting of Mg, Zn, Co, Mn, Ni, Ti and V, At least one of calcium phosphate Ca3(PO4)2 particles and aluminum phosphate AlPO4 particles exists on the surface of primary particles of the positive electrode active material, on the grain boundaries between primary particles, or on both the surface and the grain boundaries.
2. The positive electrode material for lithium ion secondary battery according to claim 1, wherein The Ca content in the positive electrode material is 100 mass ppm or more and 5000 mass ppm or less, and the Al content in the positive electrode material is 100 mass ppm or more and 5000 mass ppm or less.
3. The positive electrode material for lithium ion secondary battery according to claim 1 or 2, wherein The positive electrode material has a crystallite diameter of 80 nm or more and 150 nm or less, and a specific surface area of 6.0 m 2 / g or more and 14.0m 2 / g or less.
4. The positive electrode material for lithium ion secondary battery according to claim 1 or 2, wherein The tap density of the positive electrode material is 0.8 g / cm 3 The density of the pressed powder when the positive electrode material is compressed into a circle with a diameter of 20 mm under a pressure of 16 kN is 2.4 g / cm 3 above.
5. A method for producing a positive electrode material for a lithium ion secondary battery, which is a method for producing the positive electrode material for a lithium ion secondary battery according to claim 1 or 2, The method comprises the following steps: A crystallization step, using a metal source having a valence of 2, 3 or both and a phosphoric acid source, to obtain crystallized particles through a crystallization reaction; A water washing step, washing and drying the crystallized particles to obtain a precursor of the positive electrode active material; a mixing step of mixing the precursor of the positive electrode active material, a lithium source and a carbon source to obtain a raw material mixture; and a calcining step of calcining the raw material mixture in a non-oxidizing atmosphere to obtain a positive electrode material containing the positive electrode active material; In the crystallization process, one or more selected from the group consisting of a Ca source and an Al source are added to the crystallization so that at least one of the calcium phosphate Ca3(PO4)2 particles and the aluminum phosphate AlPO4 particles is present on the surface of the primary particles of the obtained crystallization particles, on the grain boundaries between the primary particles, or on both the surface and the grain boundaries.
6. A positive electrode for a lithium ion secondary battery, comprising: an aluminum current collector, and a positive electrode composite material layer formed on the aluminum current collector, The positive electrode composite material layer contains the positive electrode material for a lithium ion secondary battery according to claim 1 or 2.
7. A lithium ion secondary battery comprising at least a positive electrode, a negative electrode and an electrolyte, The positive electrode is the positive electrode for a lithium ion secondary battery according to claim 6.
Citation Information
Patent Citations
Cathode active substance and nonaqueous electrolyte battery
JP2009032678A